Evolution and function analysis of interleukin-17 gene from Pinctada fucata martensii. Issue 88 (May 2019) - Cao, Yanfei; Yang, Shuai; Feng, Chuzhang; Zhan, Waner; Zheng, Zhe; Wang, Qingheng; Deng, Yuewen; Jiao, Yu; Du, Xiaodong
Abstract: Interleukin-17 (IL-17) is a proinflammatory cytokine that plays an important role in immune responses. In this study, we identified 57 IL-17 genes from the genomes of six marine invertebrates, including Pinctada fucata martensii, Crassostrea gigas, Lottia gigantea, Capitella teleta, Mizuhopecten yessoensis, and Mytilus galloprovincialis . Phylogenetic analysis showed that all invertebrate IL-17 genes were clustered into one group, implying that invertebrate IL-17 evolved from one common ancestral gene. From the extron–intron analysis, we found many intronless IL-17 genes in mollusks, which may be caused by retroposition. Tissue and development transcriptomic analysis showed that the expression of PmIL-17 was tissue and developmental stage-specific. Moreover, we cloned the full length of the IL-17-2 gene from P. f. martensii (PmIL-17-2) and explored its function in the immune response. The full-length cDNA of PmIL-17-2 is 719 bp, containing an open reading frame of 564 bp, a 5′ -untranslated region (UTR) of 31 bp, and a 3′ -UTR of 124 bp with a 30 bp poly (A) tail. PmIL-17-2 had a strong response to lipopolysaccharide (LPS), indicating that the PmIL-17-2 participates in innate immune responses. In situ hybridization of hemocytes showed that PmIL-17-2 was mainly produced by granulosa cells, and the number of the stained granulosa increased after LPS stimulation. These results lay the foundation for the research of IL-17 family in marine invertebrates. Highlights: A total of 57 IL-17 genes were identified from 6 marine invertebrates. IL-17 expression in pearl oyster was tissue and developmental stage specific. IL-17s in invertebrates originate from the same ancestral gene. PmIL-17-2 is involved in the innate immune response after LPS stimulation.